The Mediating Role of Good Corporate Governance in the Relationship Between Capital Structure, Investment Opportunity Set, Corporate Social Responsibility, and Firm Value - Suryadi, Nanda; Yusnelly, Arie; Zahra, Tiara Aulia; Firmansyah, Muhammad; Castro, Jose Antonio Lopez (Research in Accounting Journal (RAJ), 2025)
This study aims to provide empirical evidence on the mediating role of Good Corporate Governance (GCG) in the relationship between capital structure, investment opportunity set (IOS), corporate social responsibility (CSR), and firm value in state-owned enterprises listed on the Indonesia Stock Exchange during the 2019–2024 period. The population comprised all 24 listed state-owned enterprises, from which 14 firms were selected using purposive sampling based on predetermined criteria. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0, applying both outer and inner model evaluations. The findings indicate that CSR and capital structure do not have a direct significant effect on firm value, whereas the investment opportunity set positively influences firm value. Furthermore, Good Corporate Governance strengthens the relationship between CSR and firm value as well as between capital structure and firm value. However, GCG does not moderate the relationship between the investment opportunity set and firm value. These findings highlight the strategic importance of governance mechanisms in enhancing the value relevance of corporate financial and social policies within state-owned enterprises.